2021
DOI: 10.1016/j.jtocrr.2020.100137
|View full text |Cite
|
Sign up to set email alerts
|

Brief Report: Risk Prediction Model Versus United States Preventive Services Task Force 2020 Draft Lung Cancer Screening Eligibility Criteria—Reducing Race Disparities

Abstract: Introduction: Eligibility criteria for lung cancer screening based solely on age and smoking history are less sensitive than validated risk prediction models. The U.S. Preventive Services Task Force (USPSTF) has proposed new guidelines to improve the sensitivity for selecting high-risk individuals and to decrease race disparity. In this retrospective study, termed the Chicago Race Eligibility for Screening Cohort, we compare the sensitivity of the proposed USPSTF2020 criteria versus the PLCOm2012 risk predicti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 9 publications
3
12
0
Order By: Relevance
“…Compared with USPSTF criteria, the PLCOm2012 model with equivalent threshold has been shown to reduce Black versus White race disparities in lung cancer participant selection. 24,34 In this study, the number of minority race groups was too small to analyse separately. This analysis reflects 2•3 years mean follow-up, not 6 years of follow-up for determining lung cancer risk.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Compared with USPSTF criteria, the PLCOm2012 model with equivalent threshold has been shown to reduce Black versus White race disparities in lung cancer participant selection. 24,34 In this study, the number of minority race groups was too small to analyse separately. This analysis reflects 2•3 years mean follow-up, not 6 years of follow-up for determining lung cancer risk.…”
Section: Discussionmentioning
confidence: 94%
“…In addition, the CREST study analysis of USPSTF2021 versus PLCOm2012 threshold of at least 1·0% at 6 years (equivalent threshold) found that sensitivity differences remained (68·6% vs 79·1%; p<0·0001). 19 , 20 , 34 Expanding the USPSTF criteria by lowering age and pack-year entry thresholds is unlikely to overcome categoirical eligibility design limitations.…”
Section: Discussionmentioning
confidence: 99%
“…The PLCO m2012 model has been well-validated in selecting high-risk individuals for lung cancer screening (8,9) and includes the following variables: age, race or ethnicity, education, body mass index, chronic obstructive pulmonary disease (COPD), personal history of cancer, and family history of lung cancer as well as smoking status, intensity, duration, and quit time. Risk-based screening through PLCO m2012 reduced racial and ethnic disparities in screening eligibility within observational cohort and simulation studies compared with the 2013 (10,11) and 2021 USPSTF criteria (12). However, these assessments primarily evaluated disparities among African American individuals (12); further assessments among other racial and ethnic groups are lacking.…”
mentioning
confidence: 99%
“…Risk-based screening through PLCO m2012 reduced racial and ethnic disparities in screening eligibility within observational cohort and simulation studies compared with the 2013 (10,11) and 2021 USPSTF criteria (12). However, these assessments primarily evaluated disparities among African American individuals (12); further assessments among other racial and ethnic groups are lacking.…”
mentioning
confidence: 99%
“…For this study of sex disparities in screening eligibility, we retrospectively analyzed data from the Chicago Race Eligibility for Screening Cohort (CREST) that have been previously described. 28,29 Briefly, the cases were from a large consecutive case series obtained from the University of Illinois at Chicago Hospital's Cancer Registry. This cohort of a complete and representative lung cancer case series was derived from an urban, community-based thoracic oncology practice at the University of Illinois Hospital & Health Sciences System between 2010 and 2019.…”
Section: Methodsmentioning
confidence: 99%